Forecasting Political Disruption: The Impending Demographic Bonus in Indonesia. - Fathiya , Atikah Najra (As- Sakinah Law Firm & Society of Visual Informatics, 2023)
A demographic bonus is expected in Indonesia between 2030 and 2045 when people of productive age (16-65 years old) will dominate the country's economic and political systems. The purpose of this study is to determine whether the demographic bonus has the potential to produce turmoil in Indonesian politics. This study is based on the 'political demography' idea, which states that having a large number of young people in a country destabilizes its political structure. Three reasons contribute to this: the democratic and political system, economic factors, and prejudice against specific ethnicities and religions. According to the findings of this study, the author discovered factors that have the potential to cause turbulence in Indonesia's political system, such as Indonesia's unstable democratic and political system, as well as discrimination that can lead to protests from minorities against their unequal participation in Indonesian politics.